Clinicopathological Spectrum and Management of Lacrimal Gland Tumors: A Five-Year Retrospective Analysis from an Indonesian Tertiary Center - Agustin Virajati Negoro; Mardijas Efendi; Ardizal Rahman (HM Publisher, 2025)
Background: Lacrimal gland tumors are a rare and heterogeneous group of neoplasms, representing a significant diagnostic and therapeutic challenge. Regional data, particularly from Southeast Asia, is sparse. This study aims to define the clinicopathological spectrum, radiological features, and management strategies for lacrimal gland tumors at a major tertiary referral center in Indonesia. Methods: A retrospective, cross-sectional analysis was conducted on all patients with histopathologically confirmed lacrimal gland tumors treated between January 2019 and June 2024. Data extracted from medical records included demographics, detailed clinical presentations (visual acuity, proptosis, pain scores), radiological findings from computed tomography (CT) and magnetic resonance imaging (MRI), definitive histopathological diagnoses with immunohistochemical profiles, and treatment modalities with short-term outcomes. Descriptive statistics and comparative analyses were performed. Results: A total of 35 patients (19 male, 16 female; mean age 48.2 ± 16.5 years) were included. Non-epithelial lesions (88.6%) were more common than epithelial tumors (11.4%). The most prevalent diagnosis was idiopathic orbital inflammation (IOI) (n=12, 34.3%), followed by lymphoproliferative disorders (n=11, 31.4%). Adenoid cystic carcinoma (ACC) was the most frequent malignant epithelial tumor (n=3, 8.6%). Superior eyelid edema was the hallmark of non-epithelial lesions (83.9%), whereas proptosis (mean 6.2mm) and severe pain (mean VAS 7.3/10) were characteristic of ACC. Radiological findings were highly correlative, with IOI showing diffuse gland enhancement and ACC demonstrating bone erosion and perineural invasion. Management was tailored to histology, with corticosteroids for IOI, radiotherapy for lymphomas, and radical surgery for ACC. Conclusion: In this Indonesian cohort, lacrimal gland tumors are predominantly non-epithelial, with inflammatory and lymphoproliferative conditions being most common. A high index of suspicion for malignancy, particularly ACC, is warranted in patients presenting with pain and proptosis. Integrating clinical, radiological, and pathological data is paramount for accurate diagnosis and effective management.